Centroid Moment Tensor Catalog With 3D Lithospheric Wave Speed Model: The 2016–2017 Central Apennines Sequence. Issue 4 (9th April 2022) - Artale Harris, P.; Scognamiglio, L.; Magnoni, F.; Casarotti, E.; Tinti, E.
Abstract: Moment tensor inversions of broadband velocity data are usually managed by adopting Green's functions for 1D layered seismic wave speed models. This assumption can impact on source parameter estimates in regions with complex 3D heterogeneous structures and discontinuities in rock properties. In this work, we present a new centroid moment tensor (CMT) catalog for the Amatrice‐Visso‐Norcia (AVN) seismic sequence based on a recently generated 3D wave speed model for the Italian lithosphere. Forward synthetic seismograms and Fréchet derivatives for CMT‐3D inversions of 159 earthquakes with M w ≥ 3.0 are simulated using a spectral‐element method (SEM) code. By comparing the retrieved solutions with those from time domain moment tensor (TDMT) catalog, obtained with a 1D wave speed model calibrated for Central Apennines (Italy), we observe a remarkable degree of consistency in terms of source geometry, kinematics, and magnitude. Significant differences are found in centroid depths, which are more accurately estimated using the 3D model. Finally, we present a newly designed parameter, τ, to better quantify and compare a‐posteriori the reliability of the obtained MT solutions. τ measures the goodness of fit between observed and synthetic seismograms accounting for differences in amplitude, arrival time, percentage of fitted seconds, and the usual L2‐norm estimate. The CMT‐3D solutions represent the first Italian CMT catalog based on a full‐waveform 3D wave speed model. They provide reliable source parameters with potential implications for the structures activated during the sequence. The developed approach can be readily applied to more complex Italian regions where 1D models are underperforming and not representative of the area. Plain Language Summary: The moment tensor (MT) is a mathematical representation of the movement on a fault during an earthquake, and of the size, or magnitude, of the event. Such tensor is often described through the beachballs, a graphic symbol that indicates the fault orientation and the type of slip that occurs during an earthquake. Usually, seismologists use 1D wave speed models (i.e., describing only the vertical velocity of seismic waves in the Earth interior) in order to compute MTs. In recent years, due to the incredible progresses of computer sciences, also 3D models, which are able to describe lateral velocity variations, have been successfully adopted to compute MTs. In this work, we use the recently developed 3D Italian wave speed model "IMAGINE_IT" (" Im25 " for brevity) to compute the MT solutions for the Amatrice‐Visso‐Norcia (AVN) 2016–2018 earthquakes with magnitude larger than 3. This seismic sequence ruptured almost 80 km of the Apennines normal faults and resulted in 299 casualties and >20, 000 homeless. Our newly developed MT catalog allows us to better understand the characteristics of the faults activated during the seismic sequence and to provide more reliable source parameters as magnitude and depth. Key Points: A new centroid moment tensor catalog for Central Italy earthquakes has been built based on a 3D wave speed model for the Italian lithosphere Moment magnitude, kinematic source parameters, and centroid depths inferred with a 3D wave speed model are accurately estimated The goodness of moment tensor solutions is tested via a newly designed quality factor